Um olhar fenomenológico no exercício do poder das relações interpessoais nas instituições escolares : o gosto amargo do mel - Pires, Sonia Aparecida da Silva de Lara (2011)
This phenomenological qualitative research aims to examine the conflicts and seeking to understand the dynamics of interpersonal relationships between the other and me, under the focus of labor relations in educational institutions. The research takes as its central reference a summary of Emmanuel Mounier mature work - Personalism; a reference work which has a Husserlian philosophical inspiration, when Husserl had already been enriched by his readings about Merleau-Ponty XX. In Brazil, the educator Paulo Freire draws his theoreticalmethodological matrix inspired, broadly speaking, in the tradition of those dialectical-phenomenological three authors. In loyalty to this philosophical track, we‘ll follow the world of educators life evaluating its the political and relational dimension, their work, through questionnaires and life histories with managers and teachers, in the foothills of the institutionalized culture present in state public schools of the city of Diamantino- Mato Grosso / Brazil. We are going to collate such conflicts and rereading them, providing new meanings to them in light of the notes of Mounier and Freire, which gain political content and open possibilities of expanding the senses and possible ways to overcome. There are no impersonal relationships in the strong hierarchical culture inculcated by the State in the theories of management control and direction, as well as through established academic standards that sets desirable patterns of behavior, distinguishing functions, ranking people, organizing labor relations consolidating the interests of capital. In these foothills, this depersonalization, the instrumental conception of human beings acquired an imposed and exterior rationality, wounding, essentially, the person. Concept expensive to Mounier, who denounces the implosion of the educational scope by the violence of a Bonaparte‘s state, whereby, the public, the subject of rights, the political dimension of human beings are bleeding to death because that person is the holder of relationship, which makes it complete, politics. This is our complaint, supported by Mounier and Paulo Freire.